A simple and universal quasi-modular cloning system using NEBuilder® HiFi DNA assembly kit - Toleco, M Rey (BioTechniques, 2025)
Modular cloning has transformed synthetic biology by enabling rapid assembly of standardized DNA parts, but its effectiveness is often limited to well-characterised model organisms. Here, we expand the utility of the NEBuilder® HiFi DNA Assembly Kit (New England Biolabs) into a quasi-modular system that uses single-stranded oligonucleotide bridges to assemble reusable DNA fragments without the need for restriction enzymes. Using the anaerobic gut eukaryote Blastocystis ST7-B as a test case, we constructed and reassembled vectors with diverse promoter-terminator combinations. These results underscore the versatility of the method and its potential to accelerate genetic tool development in non-model biological systems